2018
DOI: 10.1177/0018726718779121
|View full text |Cite
|
Sign up to set email alerts
|

Relational job crafting: Exploring the role of employee motives with a weekly diary study

Abstract: In this weekly diary study, we integrated research on job crafting to explore the associations between expansion and contraction oriented relational job crafting (RJC), work engagement and manager-rated employee behaviors (work performance and voice). Furthermore, we investigated cross level moderations of prosocial and impression management motives on our proposed associations. We tested our hypotheses with matched data collected over seven weeks in Istanbul, Turkey. The results from multilevel analyses revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 78 publications
1
73
3
Order By: Relevance
“…Employees' motivation to craft their job also influence the effect of crafting. Rofcanin et al () indicated that the positive relationship of approach resources crafting (i.e., expansion‐oriented relational crafting) and work engagement was stronger for employees with lower impression management motives. In addition, research indicated that approach crafting might be more beneficial to employees who experience rough times, such that the positive relationship between approach crafting and work attachment was stronger for employees who were rated as poor performers or felt job insecurity (Wang, Demerouti, et al, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
See 2 more Smart Citations
“…Employees' motivation to craft their job also influence the effect of crafting. Rofcanin et al () indicated that the positive relationship of approach resources crafting (i.e., expansion‐oriented relational crafting) and work engagement was stronger for employees with lower impression management motives. In addition, research indicated that approach crafting might be more beneficial to employees who experience rough times, such that the positive relationship between approach crafting and work attachment was stronger for employees who were rated as poor performers or felt job insecurity (Wang, Demerouti, et al, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…Although it is assumed that job crafting aims to benefit individuals themselves, approach crafting has also been found to benefit organizations because it is negatively related to turnover intentions (Esteves & Lopes, 2017b;Rudolph et al, 2017) and positively related to higher level of intention to stay (Rofcanin, Berber, Koch, & Sevinc, 2016), organizational commitment (Cheng et al, 2016;Rofcanin et al, 2016;Wang, Demerouti, Le Blanc, & Lu, 2018), and enhanced motivation to continue working beyond retirement age among older workers (Lichtenthaler & Fischbach, 2016b). With enhanced personjob fit and motivation as a result of approach crafting, it is not surprising that approach crafting is also associated with higher levels of task and contextual performance (Lichtenthaler & Fischbach, 2016a;Rofcanin, Bakker, Berber, Gölgeci, & Las Heras, 2018;Rudolph et al, 2017).…”
Section: Outcomes Of Approach Craftingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, job crafting research grounded in the job demands-resources (JD-R) model centers on employees' actual behaviors to either decrease job demands or increase job resources (Bakker & Demerouti, 2017;Nielsen & Abildgaard, 2012;Tims & Bakker, 2010;Zhang & Parker, 2018). Others have emphasized crafting behaviors in terms of approach or avoidance in resolving experienced discrepancy (Bruning & Campion, 2018;Mäkikangas, 2018;Rofcanin, Bakker, Berber, Gölgeci, & Las Heras, 2018). The organizing principle here distinguishes types of regulatory focus (i.e., approach/avoid; promote/prevent) that encompass the different domain-specific behaviors.…”
Section: Crafting Behaviors and Cognitionsmentioning
confidence: 99%
“…In our model, we integrate crafting efforts in line with regulatory focus (Elliot, 2006;Higgins, 1998) as it represents a broader level of organization (see also Bindl et al, 2018;Bruning & Campion, 2018;Rofcanin et al, 2018). We adopt the hierarchical structure of crafting proposed by Zhang and Parker (2018) and define approach-focused crafting as intended to add various aspects to work or non-work roles to satisfy psychological needs, whereas avoidance-focused crafting refers to diminishing undesirable aspects of a work or non-work role to satisfy psychological needs.…”
Section: Crafting Effortsmentioning
confidence: 99%